Recapturing the fundamental social right to education within the context of punitive incarceration through administrative law - Bloj, Vanesa Ingrid (Universidad Nacional del Litoral, 2019)
We will address the right to education within the context of punitive incarceration with the objective of demonstrating that, in these circles, it comes to be viewed as a “benefit”. This methodology consists of an analysis of the “pathologies” of the system. We will begin with a dogmatic abstract study that allowed us to conclude that the “stimulus” installed in Argentina’s law is unconstitutional because it is unreasonable. Then, after warning of indications revealing failures in this system, we present field research from the University Education in Prisons Program in our University, through interviews with its members and a visit to a collegiate classroom in the Coronda Penal Institution where we spoke with students. In the field study, we proved our suspicions to be true and learned of the bureaucratic obstacles inherent in the penal system that are faced by students deprived of their liberty. With this, we came to confirm that it is not solely an issue of normative deviations, but also that correlations are present in its application. Finally, we conclude with the necessity of overcoming the obstacles at hand and, with purposeful intentions, think of ways to overcome them.